Paired box 5 is a frequently methylated lung cancer tumour suppressor gene interfering β‐catenin signalling and GADD45G expression. Issue 5 (4th February 2016) - Zhao, Lijuan; Li, Shuman; Gan, Lin; Li, Chunhong; Qiu, Zhu; Feng, Yixiao; Li, Jisheng; Li, Lili; Li, Chen; Peng, Weiyan; Xu, Can; Wang, Zhenyu; et al.
Abstract: Recent studies suggest that paired box 5 (PAX5) is down‐regulated in multiple tumours through its promoter methylation. However, the role of PAX5 in non‐small cell lung cancer (NSCLC) pathogenesis remains unclear. The aim of this study is to examine PAX5 expression, its methylation status, biological functions and related molecular mechanism in NSCLC. We found that PAX5 was widely expressed in normal adult tissues but silenced or down‐regulated in 88% (7/8) of NSCLC cell lines. PAX5 expression level was significantly lower in NSCLC than that in adjacent non‐cancerous tissues ( P = 0.0201). PAX5 down‐regulation was closely associated with its promoter hypermethylation status and PAX5 expression could be restored by demethylation treatment. Frequent PAX5 promoter methylation in primary tumours (70%) was correlated with lung tumour histological types ( P = 0.006). Ectopic expression of PAX5 in silenced lung cancer cell lines (A549 and H1975) inhibited their colony formation and cell viability, arrested cell cycle at G2 phase and suppressed cell migration/invasion as well as tumorigenicity in nude mice. Restoration of PAX5 expression resulted in the down‐regulation of β‐catenin and up‐regulation of tissue inhibitors of metalloproteinase 2, GADD45G in lung tumour cells. In summary, PAX5 was found to be an epigenetically inactivated tumour suppressor that inhibits NSCLC cell proliferation and metastasis, through down‐regulating the β‐catenin pathway and up‐regulating GADD45G expression.